Growth, inequality and politics revisited a developing country case - Balisacan, Arsenio M.; Fuwa, Nobuhiko
Key issues in the empirical study on growth are addressed using provincial data in the Philippines. We find a high rate of absolute convergence, a positive relationship between inequality and growth, and a positive relationship between politcal competitiveness ang growth.
A copy is also available at the UPSE Library Archives (Faculty Publications).
Keywords: Economic development -- Philippines